Innovative Interaction of Economic entities in the Cluster formations of Kazakhstan - Turekulova, D.M.; Muhambetova, L.K.; Chimgentbaeva, G.K. (BUKETOV BUSINESS REVIEW, 2017)
In modern literature, the term "cluster" is understood in different ways, which is the recognition of researchers to give a comprehensive definition is difficult. The term "cluster" is used in a variety of forms in the context of the economic scope. On the basis of generalization of existing approaches highlighted three broad definition of the cluster, which allowed him to clarify the essential features and the most important conditions for the occurrence. In the high technology sectors of industrial-innovative development of Kazakhstan the special role is played - innovation clusters, industrial clusters, specializing in high-tech industries. Innovative cluster systems are characterized by the features: the presence of a large company - the leader, the territorial localization, stability relations of economic entities - participants of the cluster system, the long-term coordination of interaction between participants of the system within the production programs, innovative processes, quality control. Presented structure of the functional interaction of innovative economic subjects in cluster formations shows a set of economic development of production cycles in the regional economy in the form of conditional formula: tradition - investment - innovation - investment. Centralized model of economic organization prevailing in the territories of Kazakhstan is characterized by the dominance of large-scale industrial production, combined in the corporate structure. However, at the present stage of development of the country becomes the most promising network model of territorial and economic organization, based on the mobilization of resources across the network by cluster development. The need for the creation of regional clusters is predetermined by a pronounced regional context of the modern development of the country. Regional grouping implemented on the basis factors such as innovation and patent activity; human, private and social capital; regional accessibility; the regional concentration of the business; GRP per capita. Carried out clustering regions of Kazakhstan allowed to identify the main directions of improving their competitiveness.